system dynamic modelling for e-government Implementation, a case study in Bandung City, Indonesia - Farah Alfanur, Takeshi Arai, Utomo Sarjono (ITB, 2010)
Govermnments araound the word have developed e-Govermment program hoping to obtain great benefits. However, many e-Goverment projects have failed to deliver their promises. Some of such failures are thought to be the results of lack of understanding baoutthe relationships among 'technologies', 'informationuse', 'organizational factors', 'social contexts involved in the selection, implementation and use of information and comunication technologies (ICT)'. These factors stated above might have produced mismatches and unintended consequences. This research dras on not a few precedent studies as to those factors, and the case of the e-Goverment program in Bandung municipality, Indonesia, is assumed as a typical example of municipalities in developing nations. In this study, a simulation tool which helps to find the best way to create the efficient and useful e-Goverment is presented. In particular, the modal, which is the core of the simulation tool, takes not only the supply side perspective which describes the mechanisme of crating and operatng the e-Government system but also the demandside perspective which explains the people's intention of communicating with the e-Goverment and their behaviors toward it. The simulation tool is constructed based on System Dynamics as an integrated and comprehensive approach to understand the e-Goverment and its use. ecause of lack of suitable statistical data, simulations were carried out by using subjectively estimated but plausible values of parameters after the sensitivity analysis. From the results of simulations, vey complocated trade-off relationships amongthe allocated project budgets to different types of program were suggested.